Pengaruh Orientasi Kewirausahaan, Kinerja Pemasaran, dan Kapabilitas TIK Terhadap Keunggulan Bersaing Pada Pelaku UMKM di Sentra Industri Sepatu Cibaduyut Kota Bandung - Mochammad Rifky Pamungkas; Muhamad Rizal; Ria Arifianti; Asmaul Husna (Bahtera Inovasi, 2021)
Covid-19 penetrates into Indonesia to have an impact on Business, Micro, Small and Medium Enterprises (MSMEs). One of the MSMEs affected by the Covid-19 pandemic is the Cibaduyut Shoe Industry Center. This has an impact on business, marketing, information and the competitiveness of MSME players in Cibaduyut. So the research objective is to find and determine the effect of entrepreneurial orientation, marketing performance, and ICT capabilities on competitive advantage. The research method used is quantitative with the research sample being SMEs in Cibaduyut and analysis using Structural Equation Modeling-Partial Least Square. While the results of the study provide results for the greatest influence on the ICT capability variable of 44.9%. The conclusion in this study is that the entrepreneurial orientation variable and marketing performance do not have a significant effect on competitive advantage, while the ICT capability variable has a significant effect.